Changes in K Value and Biogenic Amines During Storage of Atlantic Mackerel (Scombes scomberus) in Ice - P.T., Mathew; Ryder, John M.; K., Gopakumar (Fishery Technology, 2025)
Determination of K value in conjunction with sensory evaluation serves as a good index of the freshness of fish. In this study, the above parameters were used to determine the freshness of Atlantic mackerel (Scombes scomberus) during storage in ice. K value showed a steady increase from 23 to 78 during ten days of storage in ice. No biogenic amines such as putrescine, cadaverine, tyramine, spermine and spermidine were detected in the fish during this period